Pelatihan Skrining Masalah Kesehatan Jiwa Meningkatkan Pengetahuan Kader: Studi Kuasi-Eksperimental - Zacky Aulia Rahman; Warih Andan Puspitosari; Melly Novalia (Universitas Hang Tuah Pekanbaru, 2025)
The burden of mental health problems is increasing, necessitating early diagnostic confirmation and intervention. Screening for mental health problems is a preventive strategy that can be carried out by trained community health cadres; however, cadres’ performance in screening practice remains variable. This study aimed to analyze the effectiveness of mental-health screening training on cadres’ knowledge and to examine whether demographic factors influence training effectiveness. One-group pretest–posttest quasi-experimental design is used and involving 55 community health cadres recruited via purposive sampling. The research instrument was a questionnaire consisting of nine statements to measure the level of knowledge of cadres regarding screening for mental health problems, the validity and reliability of which had been tested.Changes in knowledge were tested using the Wilcoxon Signed-rank test. Training effectiveness was assessed with normalized gain and compared across age group, marital status, and occupation using the Mann–Whitney U test, and education level using the Kruskal–Wallis test. Results showed a significant increase in knowledge after the training (p < 0.001). There were no significant differences in effectiveness by occupation (p = 0.640), marital status (p = 0.942), age group (p = 0.342), or education (p = 0.698). Mental-health screening training improves cadres’ knowledge, while the demographic factors do not affect training effectiveness. Studies with control groups and effect-size reporting are recommended to strengthen the inference.